Effect of 6-Month Isotretinoin Treatment on 25-Hydroxyvitamin D Levels in Patients With Acne Vulgaris - Gülbahar Saraç; Tuba Tülay Koca; Serpil Şener; Gülden Hakverdi (National Scientific Medical Center, 2018)
Objectives: Acne is a chronic inflammatory disease that affects the pilosebaceous units of the skin. Isotretinoin is a derivative of the synthetic 13-cis-retinoic acid and is an efficient drug for acne treatment. In clinical studies, the negative effects of long-term and short-term isotretinoin use on vitamin D levels and bone metabolism restrict its use. In this study, the effect of isotretinoin treatment on vitamin D levels was examined in patients with acne vulgaris. Material and Methods: Ninety patients with clinically diagnosed acne vulgaris who came to the Malatya Research and Training Hospital Dermatology Clinic participated in this study. Patients who had been using any systemic drug for the previous month or who had any systemic disease were not included in the study. Patients with abnormalities in calcium (Ca), alkaline phosphatase (ALP), and parathyroid hormone (PTH) levels, which affect vitamin D metabolism, also were not included in the study. Patients were treated first with 0.5 to 1.0 mg/kg (per kilogram of body weight) doses of isotretinoin, with the aim of total dosage of 120 mg/kg. The patients' 25-hydroxy vitamin D3 [25'(OH) vit D3] levels were measured before treatment and at the sixth month of treatment. Results: Among the 90 patients who participated in the study, 51 (56.7%) were female, and 39 (43.3%) were male, with an age range of 16 to 50 years (mean ±standard deviation) age, 23.55±5.58 years. Eight patients dropped out of the study. The patients' (mean ± standard deviation) 25'(OH) vit D3 level was 18.28±9.92 before treatment and 13.28±7.78 at the sixth month of treatment (p=0.000). Conclusion: The negative effect of isotretinoin on vitamin D levels and bone metabolism has been shown in previous studies. In this study, 25'(OH) vit D3 levels decreased significantly in patients treated with isotretinoin in the long term (p>0.000).